Enhancing cement-based inorganic coating performance through the integration of graphene-titanium dioxide composite nanofibers - Xiang-fei Wang; Chun Pei; Liangliang Wei; Ji-Hua Zhu (Case Studies in Construction Materials)
In pursuit of advancing sustainable building practices, this research focuses on enhancing the photocatalytic capabilities of concrete structures. A cement-based inorganic coating, designed for photocatalysis, was developed and systematically evaluated for its efficacy in degrading organic pollutants, as exemplified by methylene blue (MB) solution photocatalysis. The employed photocatalyst comprises graphene-modified TiO2 nanofibers prepared via the electrospinning technique, with different proportions of anatase and rutile phases achieved through controlled heat treatment. A TiO2@graphene sample composed entirely of anatase was obtained by heat treatment at 550 °C, achieving an optimal degradation efficiency of 76.2 % under simulated light irradiation at 1.5 W/m2, and TiO2 composed of 9.5 % anatase as well as 90.5 % rutile was obtained at 750 °C, with a photocatalytic capacity comparable to that of the 550 °C sample. The 650 °C sample, on the other hand, contained 87.1 % of the anatase and 16.9 % rutile phases, with the lowest photocatalytic efficiency of 70 %. Photoluminescence (PL) and diffuse reflectance spectroscopy (DRS) tests revealed that the incorporation of graphene mitigated electron-hole recombination rates, resulting in a redshifted spectrum. This observation confirmed the enhanced activity of the catalyst in visible light, thereby significantly augmenting the coating's effectiveness on building surfaces. Furthermore, pencil hardness tests confirmed the improved wear resistance of the photocatalyst-infused coating. These findings contribute valuable insights into the development of cement-based inorganic coatings modified with graphene-TiO2 nanofibers, showcasing their potential as sustainable and resilient building materials with improved photocatalytic and mechanical properties.